BUILDING EVALUATION PARTNERSHIPS WITH TRIBAL COMMUNITIES FOR HOME VISITING. Issue 3 (9th May 2018) - Ayoub, Catherine C.; Geary, Erin; Londhe, Rucha; Hiratsuka, Vanessa; Roberts, Erica
ABSTRACT: The goal of this current descriptive study was to examine the roles and relationships of evaluators with the tribal communities in which they work. First, we describe a participatory community research model with a strong capacity‐building component as the standard for assessing successful working partnerships between evaluators, programs, tribes, and tribal organizations. This model serves as a yardstick against which we examine the success and challenges of program–evaluation partnerships. Second, we report on a survey of tribal Maternal, Infant, and Early Childhood Home Visiting program leaders and outline their impressions of successes and challenges related to program–evaluation partnerships. Survey participants discussed the importance of working with evaluators who have deep investment in and understanding of the tribal community; respect for cultural relevance and honor for cultural ways; collaboration that includes transparency, trust, and translation of research for community leaders and members; a focus on strength‐based design without losing the need to consider challenges; and relationships of mutual trust that can weather addressing stressors when issues of conflict, limited resources, and/or mixed expectations arise.